PEMANFAATAN CAKAR AYAM SEBAGAI BAHAN DASAR GELATIN DALAM PEMBUATAN EDIBLE FILM - Irma Wardani Irma Wardani (Universitas Islam Batik Surakarta, 2012)
The objective of this research was to know influence of plasticizer types with the concentrations to characters edible film type B gelatin from chicken claw and determines edible film with good physical and mechanical properties. Randomized Complete Block Design (RCBD) with single factor was used in this research which consisted of A (sorbitol 20%), B (sorbitol 22,5%), C (sorbitol 25%), D (glycerol 4,49%), E (glycerol 6,15%), E (glycerol 7,38%), F ( polyethylene glycol 400 4,496%), G (polyethylene glycol 400 5,62%), H (polyethylene glycol 400 6,74%). The result of edible film to analyse film thickness, tensile strength, elongation, Water Vapor Transmision Rate (WVTR) and film solubility in water. Result of this research showed that plasticizer with concentrations influence on to value WVTR and solubility of film in water, but doesn't have an effect on to film thickness, tensile strength, and elongation of edible film. Edible film with greather WVTR resulted from sorbitol concentration of 20% with value WVTR 20,3472 g.mm/m2.8hours, film solubility in water 85,5147%, tensile strength 0,13 N, elongation 8,58% and thickness of film 0,18 mm